2017
DOI: 10.1155/2017/1524023
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Energy‐Related Carbon Emissions in Beijing‐Tianjin‐Hebei Region

Abstract: Beijing-Tianjin-Hebei is a typical developed region in China. The development of economy has brought lots of carbon emissions. To explore an effective way to reduce carbon emissions, we applied the Logarithmic Mean Divisia Index (LMDI) model to find drivers behind carbon emission from 2003 to 2013. Results showed that, in Beijing, Tianjin, and Hebei, economic output was main contributor to carbon emissions. Then we utilized the decoupling model to comprehensively analyze the relationship between economic outpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…This region is facing serious environmental issues, which makes it very important in analyzing how the socioeconomic factors affect EICE divergently. In this paper, we find that traditional factors, such as energy intensity effect, contributed greatly to the decrease of EICE change across this region, which is in accordance with previous studies [43,44]. In terms of R&D factors, there was a paper [45] using the STIRPAT (stochastic impacts by regression on population, affluence and technology) model to identify that the increase of R&D output was an efficient way to reduce CO2 emissions.…”
Section: Discussionsupporting
confidence: 86%
“…This region is facing serious environmental issues, which makes it very important in analyzing how the socioeconomic factors affect EICE divergently. In this paper, we find that traditional factors, such as energy intensity effect, contributed greatly to the decrease of EICE change across this region, which is in accordance with previous studies [43,44]. In terms of R&D factors, there was a paper [45] using the STIRPAT (stochastic impacts by regression on population, affluence and technology) model to identify that the increase of R&D output was an efficient way to reduce CO2 emissions.…”
Section: Discussionsupporting
confidence: 86%
“…Román-Collado et al [ 20 ] found that the key driving factors were economic activities and population effects in Latin America, followed by fossil fuels and carbonization effects, while intensity effect was an inhibitory factor. Furthermore, some researchers analyzed the drivers of CO 2 emissions from aspects of energy structure, population size, energy intensity, economic growth, and other factors in Eastern and central China, Yangtze River Delta, and Beijing–Tianjin–Hebei Region, respectively [ 21 , 22 , 23 ]. The above studies mainly focused on countries or large-scale areas and achieved good results by analyzing the factors of CO 2 emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that the relative decoupling occurred at a high level in China. Wang et al 16 compared the decoupling states between carbon emissions and GDP in Beijing-Tianjin-Hebei between 200 and 2013. According to Vehmas et al 17 and Tapio, 13 China and the United States are the top two CO 2 emitters in the world, thus the simultaneous relationship between their economic development level and CO 2 emissions has attracted the interest of scholars.…”
Section: Literature Reviewmentioning
confidence: 99%